Renin angiotensin-aldosterone system (RAAS) blockers usage among type II diabetes mellitus patients—A Retrospective Study. Issue 3 (May 2018) - Ng, Yen Ping; Balasubramanian, Ganesh Pandian; Heng, Yi Ping; Kalaiselvan, Meera; Teh, Yu Wen; Cheong, Kin Man; Hadi, Muhammad Faiz Bin Abdul; Othman, Rosmaliza Bt
Abstract: Aims: Recent data showed an alarming rise of new dialysis cases secondary to diabetic nephropathy despite the growing usage of RAAS blockers. Primary objective of this study is to explore the prevalence of RAAS blockers usage among type II diabetic patients, secondary objectives are to compare the prescribing pattern of RAAS blocker between primary and tertiary care center and to explore if the dose of RAAS blocker prescribed was at optimal dose as suggested by trials. Materials and methods: This is a retrospective study conducted at one public tertiary referral hospital and one public health clinic in Sungai Petani, Kedah, Malaysia. Results: RAAS blockers in T2DM patients was found to be 65%. In primary care, 14.3% of the RAAS blockers prescribed was ARB. Tertiary care had higher utilization of ARB, which was 42.9%. In primary care setting, the most commonly used ACEI were perindopril (92.4%) followed by enalapril (7.6%), meanwhile perindopril was the only ACEI being prescribed in tertiary care. The most prescribed ARB was irbesartan (63.6%) and telmisartan (54.2%) respectively in primary and tertiary care. Overall, 64.9% of RAAS blockers prescribed by both levels of care were found to be achieving the target dose as recommended in landmark trials. Crude odd ratio of prescribing RAAS blocker in primary care versus tertiary care was reported as 2.70 (95% CI: 1.49 to 4.91). Conclusion: RAAS blockers usage among T2DM patients was higher in primary care versus tertiary care settings. Majority of the patients did not receive optimal dose of RAAS blockers.